Voltage-Controlled Deblocking of Magnetization Reversal in Thin Films by Tunable Domain Wall Interactions and Pinning Sites - Zehner, Jonas; Soldatov, Ivan; Schneider, Sebastian; Heller, Rene; Khojasteh, Nasrin B.; Schiemenz, Sandra; Faehler, Sebastian; Nielsch, Kornelius; Schaefer, Rudolf; Leistner, Karin (Advanced Electronic Materials, 2020)
High energy efficiency of magnetic devices is crucial for applications such as data storage, computation, and actuation. Redox-based (magneto-ionic) voltage control of magnetism is a promising room-temperature pathway to improve energy efficiency. However, for ferromagnetic metals, the magneto-ionic effects studied so far require ultrathin films with tunable perpendicular magnetic anisotropy or nanoporous structures for appreciable effects. This paper reports a fully reversible, low voltage-induced collapse of coercivity and remanence by redox reactions in iron oxide/iron films with uniaxial in-plane anisotropy. In the initial iron oxide/iron films, Néel wall interactions stabilize a blocked state with high coercivity. During the voltage-triggered reduction of the iron oxide layer, in situ Kerr microscopy reveals inverse changes of coercivity and anisotropy, and a coarsening of the magnetic microstructure. These results confirm a magneto-ionic deblocking mechanism, which relies on changes of the Néel wall interactions, and of the microstructural domain-wall-pinning sites. With this approach, voltage-controlled 180° magnetization switching with high energy-efficiency is achieved. It opens up possibilities for developing magnetic devices programmable by ultralow power and for the reversible tuning of defect-controlled materials in general.
CRIS-Team Scopus Importer:2022-04-14
Keywords: iron films; magnetic domains; magneto-ionic mechanisms; magnetoelectrics; Néel walls